Quantitative Analysis of Ultrasound Tissue Diffusion Elastography in The Diagnosis of Benign and Malignant Prostate Lesions - Guo, Jun; Liang, Lei; Zhou, Nan; Li, De-Yu (Urology Journal, 2019)
Purpose: This study aims to evaluate the value of quantitative analysis of ultrasound real-time tissue diffusion elastography in the diagnosis of benign and malignant prostate lesions. Materials and Methods: From March 2010 to June 2013, 52 patients suspected with prostate cancer based on laboratory or clinical test results and underwent prostate biopsy in our hospital were enrolled into this study. The age of these patients ranged between 45-82 years, with an average age of 67.2 ± 6.8 years. All patients underwent transrectal real-time ultrasound elastography (TRTE) before biopsy. A total of 63 prostate nodules were detected, and the 11 elastic characteristic quantities of these nodules were quantitatively analyzed via tissue diffusion quantitative analysis. The results of ultrasonography were compared with the results of operation and pathology. Result: Among these 11 characteristic quantities, which include the mean (MEAN) and standard deviation (SD), blue area ratio (AREA%), complexity (COMP), kurtosis (KURT), skewness (SKEW), contrast (CONT), equality (ENT), entropy (IDM), consistency (ASM) and correlation (CORR), except for COMP and CORR, the differences in other nine characteristic quantities between benign and malignant prostatic nodules were statistically significant (P<0.05). Among these, the AREA% and MEAN had the highest correlation, which were 0.791 and -0.791, respectively. The Youden’s index (sensitivity and specificity) of AREA% in the ROC curves was the highest, the cutoff value was 80.65% for the diagnosis of prostate cancer, sensitivity was 87.9%, and specificity was 96.6%. Conclusion: Quantitative analysis of ultrasound real-time tissue diffusion elastography is helpful in the diagnosis of benign and malignant prostate lesions, provides a relatively accurate evaluation method in clinical practice, and has broad application prospects.